Paralympic Athlete Management System / Chuah Poh Thye - Chuah , Poh Thye (2002)
The objective of PAM is to provide a web - based Paralympic Athlete Management System (PAMS) in order to provide an athlete's information and manage the athlete information when organizing the games. This system will be used by Malaysian Paralympic council (MPC) to replace their current system which is performed manually at this time being. A survey has been carried out to evaluate the existing PAM system which was developed by diploma student. The existing system have provided the basic knowledge of the requirement of PAMS and overview of the system flow. Besides, interview session also carried out with MPC, to understanding their system management in athlete information. The functions provided by PAMS are able to search on data according to the different categories. Besides, PAMS offer notable protection against unauthorized access to server, database and document through Internet Information Server. There are two types of users on PAMS: administrator and general users. Administrator can be grouped into super administrator and assistant administrator. Th authorize to do modification on data in the database while the general users is refer to staff of MPC which is not involve in the administrative. The general user only to allowed to retrieve and search on data but they forbidden to make any changes on data in the database. PAMS developed with Active Server Page technology using Internet Information Server and running on Microsoft Window 2000 Professional. Microsoft SQL 7.0 is used in database management. Other Software and development tools such as Microsoft Internet Explorer 5.0, Microsoft Visual InterDef 6.0 also be used in develop PAMS.